2003
DOI: 10.1029/2002gl016364
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap observations of mesospheric and lower thermospheric 4‐hour waves in temperature

Abstract: Lower thermospheric and upper mesospheric rotational temperatures have been derived from ground‐based measurements of the O2(0–1) and OH(6–2) nightglow emissions over Resolute Bay, Canada (74.68°N, 94.90°W) and OH(4–2) nightglow emission over Kiruna, Sweden (67.90°N, 21.10°E). From measurements taken during two nights in November, 2001, we have observed a dominant and coherent 4‐hr oscillation in both the O2 and OH airglow emission rates and rotational temperatures. The phases for the two oscillation events re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…It is an imager with narrow-band filters for the O 2 (0,1) atmospheric band and the OH (6,2) Meinel band in which radial distance on the image gives the spectrum and the tangential angle the azimuthal position on the sky. It is described in detail by Sargoytchev et al (2004) and high latitude results have been presented on a 4-h oscillation by Won et al (2003) and on mesospheric cooling by Cho et al (2004).…”
Section: Dataset Descriptionmentioning
confidence: 98%
“…It is an imager with narrow-band filters for the O 2 (0,1) atmospheric band and the OH (6,2) Meinel band in which radial distance on the image gives the spectrum and the tangential angle the azimuthal position on the sky. It is described in detail by Sargoytchev et al (2004) and high latitude results have been presented on a 4-h oscillation by Won et al (2003) and on mesospheric cooling by Cho et al (2004).…”
Section: Dataset Descriptionmentioning
confidence: 98%
“…concluded that the measured 6-h quasi-monochromatic variation of the winter mesopause represented the effect of an s ¼ 0 non-migrating tidal oscillation, though the source of the excitation remained in question. Won et al (2003) verified that the 4-h oscillation in the northern high-latitude mesosphere temperature was an s ¼ 0 non-migrating oscillation based on observations from multiple stations.…”
Section: Introductionmentioning
confidence: 53%
“…It should be noted that the low OH temperature of SATI is signiÿcant not only for our SATI in Japan, but also for other SATIs in Spain (Là opez-Gonzà alez et al, 2003), Saskatchewan (Chshyolkova, 2003), and Resolute Bay (Won et al, 2003). Detailed analyses of SATI data from Resolute Bay also suggests the importance of the empirically-determined Q-branch coe cients (G.G.…”
Section: Discussionmentioning
confidence: 88%